Habitat dan Aspek Biologi Rajungan Angin, Podophthalmus vigil (Fabricus 1798) di Teluk Lasongko, Sulawesi Tenggara - Abdul Hamid (Institut Pertanian Bogor, 2019)
The study was conducted in Lasongko Bay, Central Buton from May 2013-March 2014 with the aim of identifying habitat conditions, size distribution, growth pattern, sex ratio, and spawning season of Podophthalmus vigil (Fabricus 1798). Samplings were done monthly on six stations using a crab gillnet. The results of research showed that P.vigil were generally found on the substrate type of sand clay with the average depth range of 4.61-11.63 m and tended to be found in cloudy locations. The ranges of carapace width of male and female P. vigil were 4.13-12.39 cm and 4.75-11.64 cm, respectively. The result of Mann-Whitney test of body size showed that in P. vigil only carapace width that were found significantly different (P<0.05) between males and females, whereas the body weight and carapace length were not significantly different (P>0.05) between male and female. The growth pattern of the width carapace and body weight relationship in male P. vigil was negatively allometric, whereas in females was positively allometric. The growth patterns of the carapace length and body weight relationship in males and females P. vigil were isometric and negatively allometric, respectively. The sex ratio of P. vigil varied spatially-temporally with total sex ratio of 1:0.74. The spawning season of P. vigil did not last all year.